2014
DOI: 10.1063/1.4890504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structural and chemical anisotropy of nanostructures on droplet spreading on a two dimensional wicking surface

Abstract: When a liquid droplet is deposited onto an array of nanostructures, a situation may arise in which the liquid wicks into the space between the nanostructures surrounding the droplet, forming a thin film that advances ahead of the droplet edge. This causes the droplet to effectively spread on a flat, composite surface that is made up of the top of the nanostructures and the wicking film. In this study, we examined the effects of structural and chemical anisotropy of the nanostructures on the dynamics of droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Analysis of the results was then carried out with a semi-empirical quantitative model that separated the effects of physicochemical surface interactions and biological responses. The procedure for the fabrication of Si nanogratings in this study is similar to that previously reported for the synthesis of nanostructures on silicon (Si) and polymeric substrates [16][17][18][19] . Briefly, P-type (100) Si wafers were first cleaned with acetone and dipped in HF for 60 s to remove the native oxide.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Analysis of the results was then carried out with a semi-empirical quantitative model that separated the effects of physicochemical surface interactions and biological responses. The procedure for the fabrication of Si nanogratings in this study is similar to that previously reported for the synthesis of nanostructures on silicon (Si) and polymeric substrates [16][17][18][19] . Briefly, P-type (100) Si wafers were first cleaned with acetone and dipped in HF for 60 s to remove the native oxide.…”
Section: Introductionmentioning
confidence: 86%
“…The procedure for the fabrication of Si nanogratings in this study is similar to that previously reported for the synthesis of nanostructures on silicon (Si) and polymeric substrates. Briefly, P-type (100) Si wafers were first cleaned with acetone and dipped in hydrofluoric acid (HF) for 60 s to remove the native oxide. Four hundred nanometers of Ultra-i-123 positive photoresist was then spin coated onto the surface and baked at 110 °C for 90 s. The wafers were diced into 1 cm × 1 cm samples and exposed to interference lithography using a He–Cd laser with a wavelength of 365 nm.…”
Section: Methodsmentioning
confidence: 99%